The case of “Manuela” and “The 17+” against El Salvador: A fraud before the Inter-American Court of Human Rights and the international community - Castaldi, Ligia de Jesús (Derecho Público Iberoamericano, 2020)
This paper analyzes the facts and political context of the “Manuela” case before the Inter-American Court of Human Rights, which seeks the decriminalization of abortion in El Salvador. It also examines the facts and context of the Petition filed before the IACHR on the cases of nine women convicted of aggravated homicide against their newborn children in El Salvador. The lawsuit by the IACHR before the Court, like the Petition, accuses El Salvador of violating human rights contained in the American Convention on Human Rights by allegedly penalizing miscarriages and obstetric emergencies in the country. This paper inquires into the veracity of arguments presented in the complaint in light of existing evidence in judicial and official documents of the “Manuela” case and the cases of “The 17+”, including first instance court judgments, motions and requests before tribunals, appeals judgments, El Salvador Supreme Court opinions and IACHR reports as of 2019.